The fate of gene duplicates in the genomes of fungal pathogens. - Skamnioti, P; Furlong, R; Gurr, S (2008)
Understanding how molecular changes underlie phenotypic variation within and between species is one of the main goals of evolutionary biology and comparative genetics. The recent proliferation of sequenced fungal genomes offers a unique opportunity to start elucidating the extreme phenotypic diversity in the Kingdom Fungi.1-4 We attempted to investigate the contribution of gene families to the evolutionary forces shaping the diversity of pathogenic lifestyles among the fungi.5 We studied a family of secreted enzymes which is present and expanded in all genomes of fungal pathogens sequenced to date and absent from the genomes of true yeasts.3,4 This family of cutinases6 predates the division between the two major fungal phyla, Ascomycota and Basidiomycota.5 We discuss our molecular phylogenetic analyses, the number and sequence diversity, and gene gains and losses of cutinase family members between five Ascomycetes: the phytopathogens Magnaporthe oryzae, Fusarium graminearum and Botrytis cinerea; and the model organisms Neurospora crassa and Aspergillus nidulans.5 The functional characterization of three members of the M. oryzae cutinase family,6-10 coupled with the regulatory subfunctionalization and neofunctionalization of most gene pairs5 provide the first justification for the retention of paralogs after duplication and for gene redundancy in the genomes of fungal pathogens.